An anti-windup INDI fault-tolerant control scheme for flying wing aircraft with actuator faults. (October 2019) - Zhang, Shaojie; Meng, Qingkai
Abstract: In this paper, an anti-windup incremental nonlinear dynamic inversion (INDI) fault-tolerant scheme is proposed for flying wing aircraft with actuator faults, actuator saturation and uncertainties of aerodynamic parameters. An optimal anti-windup compensator based on nonlinear partial differential inequalities is used to compensate the actuator saturation. INDI is used to control the fault system and compensate the uncertainties of the flight dynamics. Control allocation strategy is designed in consideration of the control scheme and configuration of the control surfaces. The proposed control method can guarantee the bounded tracking of the reference signals. Simulation results are given to show the effectiveness of the proposed method. Highlights: An anti-windup incremental nonlinear dynamic inversion (INDI) fault-tolerant scheme is proposed for flying wing aircraft with actuator faults, actuator saturation and uncertainties of aerodynamic parameters. An optimal anti-windup compensator based on nonlinear partial differential inequalities is used to compensate the actuator saturation. INDI and control allocation are used to control the fault system and compensate uncertainties in consideration of the configuration of the control surfaces.